2023
DOI: 10.3390/insects14030216
|View full text |Cite
|
Sign up to set email alerts
|

Identification and Functional Characterization of General Odorant Binding Proteins in Orthaga achatina

Abstract: The olfactory system in insects are crucial for recognition of host plants and oviposition sites. General odorant binding proteins (GOBPs) are thought to be involved in detecting odorants released by host plants. Orthaga achatina (Lepidoptera: Pyralidae) is one of the most serious pests of camphor trees, Cinnamomum camphora (L.) Presl, an important urban tree species in southern China. In this study, we study the GOBPs of O. achatina. Firstly, two full-length GOBP genes (OachGOBP1 and OachGOBP2) were successfu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 38 publications
1
3
0
Order By: Relevance
“…Competitive binding assays found that the three gene functions have undergone divergence. CpomGOBP2a has a broad binding ability, possibly binding to four compounds, including geranylacetone, codlemone, butyl octanoate, and ethyl (2E,4Z)-deca-2,4-dienoate, and the result is similar to other studies, such as the AlepGOBP2 of A. lepigone [15], the SfruGOBP2 of S. frugiperda [14], the OachGOBP2 of O. achatina [19], and the HcunGOBP2 of H. cunea [17], which have a broader ligand-binding spectrum. In contrast, CpomGOBP2b could only bind to pear ester, and CpomGOBP2c was unable to bind to any compounds.…”
Section: Discussionsupporting
confidence: 84%
See 1 more Smart Citation
“…Competitive binding assays found that the three gene functions have undergone divergence. CpomGOBP2a has a broad binding ability, possibly binding to four compounds, including geranylacetone, codlemone, butyl octanoate, and ethyl (2E,4Z)-deca-2,4-dienoate, and the result is similar to other studies, such as the AlepGOBP2 of A. lepigone [15], the SfruGOBP2 of S. frugiperda [14], the OachGOBP2 of O. achatina [19], and the HcunGOBP2 of H. cunea [17], which have a broader ligand-binding spectrum. In contrast, CpomGOBP2b could only bind to pear ester, and CpomGOBP2c was unable to bind to any compounds.…”
Section: Discussionsupporting
confidence: 84%
“…GOBPs can be further classified into two classes, GOBP1 and GOBP2. The main functions of GOBPs are the perception of host volatiles and the sex pheromone, which have been reported in various moths and butterflies, including Spodoptera frugiperda [14], Athetis lepigone [15], Conogethes pinicolalis [16], Hyphantria cunea [17], Grapholita funebrana [18], Orthaga achatina [19], Papilio xuthus [20], and so on. In addition, some GOBPs have binding abilities to insecticides, such as A. lepigone [21], Spodoptera litura [22], and P. xuthus [20].…”
Section: Introductionmentioning
confidence: 99%
“…Similar results for GOBP2 binding were found in other moths. AipsGOBP2 exhibited a high binding affinity for the plant volatiles cis-3-hexen-1-ol, oleic acid, dibutyl phthalate, and β-caryophyllene [15], and OachGOBP2 had a high binding affinity for the host plant volatiles farnesol and α-phellandrene [17]. Prior research has indicated that certain specific amino acids situated within hydrophobic cavities may play a role in the ligand-binding processes of insect OBPs.…”
Section: Discussionmentioning
confidence: 99%
“…In Lepidoptera species, PBPs are believed to function in perception of female sex pheromones, while GOBPs are thought to be involved in interacting with plant odorants. For instance, GOBP2 of Agrotis ipsilon [15], GOBP2 of Spodoptera frugiperda [16], and GOBP1-2 of Orthaga achatina [17] can strongly bind to the corresponding host plant volatiles. Recently, genome editing via CRISPR-Cas9 was used to verify that the GOBPs of S. litura participate and Conogethes punctiferalis in the detection of host odorants in vivo [18,19].…”
Section: Introductionmentioning
confidence: 99%